Kata pessoal: treinamento psicofísico para atores/bailarinos por meio do judô - PINHEIRO, Silvia do Socorro Luz (Universidade Federal do Pará, 2017)
The object of this research is the judo as body practice of the actor/dancer. A hypothesis presented in this paper is that judo includes useful techniques for training the actor/dancer looking through the lens of Theatrical Anthropology. The objective is to research the judo, both technical artifice as philosophical, elements that could enrich your state pre-expressive, which is building the Personal Kata. This proposal incorporates different theoretical and practical fields: judo and theater focus on containing the principles of judo in communion with those of Theatrical Anthropology. My experience as a judo teacher was taken as reference for the study because it represents the area on the philosophical and practical foundations of judo. About methodological procedures, we chose a qualitative approach, but it has a descriptive nature, into which was conducted a bibliographic gathering. Also, the field research, involving interviews and statements; and a laboratory of training, a title of experiment. For application of this training was selected a set of techniques of judo based on criteria such as: balance, energy, contrast-stretched body, organic.